Diseases of ginger and their control with Trichoderma harzianum - Y.R. SARMA; G.V.H. JACKSON, P.P. RAJAN, S.R. GUPTA (Indian Phytopathology, 2002)
Ginger (Zingiber officina/e Rosc.), is the second most important cash crop of Sikkim. Diseases are important production constraints and often associated with Ralstonia (Pseudomonas) solanacearum, Pythium spp., Fusarium oxysporum and Praty/enchus coffeae. Pathogenicity experiments conducted, showed the involvement of Pythium sp (soft rot), Fusarium oxysporum (dry rot) and R.solanacearum (wilt) and also noticed that, Praty/enchus coffeae increased the severity of infection along with F.oxysporum. From the indirect pathogenicity experiments, the specific chemicals, targeted to particular pathogens ensured the involvement of different pathogens as well as effectiveness of chemicals on control of ginger was diseases. A biocontrol agent, T.harzianum, isolated from Sikkim was found effective in control of ginger diseases substantially.